Compactness in Lorentz sequence spaces - Sawicki, Paweł (Topological Methods in Nonlinear Analysis, 2026)
In this paper we are going to discuss compactness in Lorentz sequence spaces. Firstly, it will be shown how to define such a space, check whether a sequence belongs to it and calculate its norm. Equipped with this knowledge, we will proceed to propose usable compactness criteria for Lorentz sequence spaces, employing the concept of seminorms.